Ruminants The Husbandry, Economic and Health Aspects - Abubakar, Muhammad (IntechOpen, 2018)
It is very essential to understand the recent advances in ruminant science to recognize and control diseases and disorders in these animals. Our book, Ruminants - The Husbandry, Economic and Health Aspects, provides a concise introductory chapter and details about the main aspects of ruminants' science and production. This is the first edition of the book, so it covers the introductory level of topics, which are written specifically for veterinary students, classroom use, and practitioners who require more knowledge of dairy animal health and production. The book covers an introductory chapter and sections on husbandry and economics as well as animal health. Each book section comprises chapters from renowned experts from the area and gives readers a unique opportunity to explore the topic.